2011
DOI: 10.1371/journal.pmed.1001062
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Serological Tests for the Diagnosis of Active Pulmonary and Extrapulmonary Tuberculosis: An Updated Systematic Review and Meta-Analysis

Abstract: An up-to-date systematic review and meta-analysis by Karen Steingart and colleagues confirms that commercially available serological tests do not provide an accurate diagnosis of tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
186
2
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(200 citation statements)
references
References 51 publications
8
186
2
4
Order By: Relevance
“…(16) In a reviewed data it is found that the serological ICT test was not sufficiently predictive for use as routine diagnostic aid for Pulmonary and/or extra pulmonary tuberculosis in TB endemic areas. The test performance was universally poor and evaluated inconsistent and imprecise estimates of sensitivities and is not enough to replace AFB smear microscopy or culture (21,25,26,27,28,28,29,30,31,32). Despite of an acceptable specificity our study result also showed very poor performance with low sensitivity 0%, 55%, 15% for IgM, IgG and IgA respectively.…”
Section: Discussionmentioning
confidence: 66%
“…(16) In a reviewed data it is found that the serological ICT test was not sufficiently predictive for use as routine diagnostic aid for Pulmonary and/or extra pulmonary tuberculosis in TB endemic areas. The test performance was universally poor and evaluated inconsistent and imprecise estimates of sensitivities and is not enough to replace AFB smear microscopy or culture (21,25,26,27,28,28,29,30,31,32). Despite of an acceptable specificity our study result also showed very poor performance with low sensitivity 0%, 55%, 15% for IgM, IgG and IgA respectively.…”
Section: Discussionmentioning
confidence: 66%
“…These tests are rapid requiring only minutes to perform after growth of the organism but literature reports indicate variable performance (Martin et al, 2011;Said et al, 2011;Steingart et al, 2011;Yu et al, 2011) 6. Direct identification of M. tuberculosis from clinical specimens…”
Section: Immunoassay Methodsmentioning
confidence: 99%
“…The quest for specific and sensitive serological tests has so far failed (Steingart et al, 2011;Steingart et al, 2007). An innovative approach with high throughput screening for antibodies against the entire M. tuberculosis proteome has recently identified a small pool of antigens that are recognized in sera of patients with active tuberculosis (Kunnath-Velayudhan et al, 2010).…”
Section: Biomarkersmentioning
confidence: 99%